2008
DOI: 10.2135/cropsci2006.09.0613
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Stress Effects on Bentgrass Putting Green and Fairway Turf

Abstract: Creeping bentgrass (Agrostis stolonifera L.) has received more study and use as golf course turf than velvet bentgrass (A. canina L.). The objective of two field trials, managed as putting green and fairway turf, was to evaluate the performance of creeping and velvet bentgrass in mixed swards with annual bluegrass (Poa annua var. reptans Hausskn.) when subjected to traffic stresses. The trials were initiated on a sandy loam (fine‐loamy, mixed, mesic Typic Hapludult). Wear (no‐wear and wear) and compaction (no‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 14 publications
1
46
2
Order By: Relevance
“…The main effects of grass type were also very significant (p = 0.05), with ZG recording the lowest BD value and BG the highest. Christians [5] noted that the leaves of ZG are stiff, due to their high silica content [42], which could buffer the compactive force applied to the surface [43]. Eudoxie et al [44] also reported that the type of turfgrass cover influenced the effects of compaction on the bulk density of the underlying root zone.…”
Section: Bulk Densitymentioning
confidence: 99%
“…The main effects of grass type were also very significant (p = 0.05), with ZG recording the lowest BD value and BG the highest. Christians [5] noted that the leaves of ZG are stiff, due to their high silica content [42], which could buffer the compactive force applied to the surface [43]. Eudoxie et al [44] also reported that the type of turfgrass cover influenced the effects of compaction on the bulk density of the underlying root zone.…”
Section: Bulk Densitymentioning
confidence: 99%
“…and topdressing has been a commonly applied maintenance practice not only on golf greens and tees but also on athletic fi elds and fairways (Kowalewski et al, 2010;Samaranayake et al, 2008). Th e benefi ts gained include thatch control, reduced disease incidence, increased surface fi rmness, improved playability, improved drainage and fewer earthworm castings (Baird, 2005;Henderson et al, 2010;Henderson and Miller, 2009).…”
mentioning
confidence: 99%
“…It increases sod elasticity, functions as a buffer against border temperatures, limits weeds and increases resistance of grasses to intensive use (McCarty et al, 2005). The size of sodding and occurring mat improve elasticity of ground, limit effect of pressing force (Samaranayake et al, 2008).…”
Section: Introductionmentioning
confidence: 99%